2016
DOI: 10.1051/0004-6361/201527835
|View full text |Cite
|
Sign up to set email alerts
|

Damping profile of standing kink oscillations observed by SDO/AIA

Abstract: Aims. Strongly damped standing and propagating kink oscillations are observed in the solar corona. This can be understood in terms of mode coupling, which causes the wave energy to be converted from the bulk transverse oscillation to localised, unresolved azimuthal motions. The damping rate can provide information about the loop structure, and theory predicts two possible damping profiles. Methods. We used the recently compiled catalogue of decaying standing kink oscillations of coronal loops to search for exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
75
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 23 publications
6
75
0
Order By: Relevance
“…Ruderman & Roberts 2002;Goossens et al 2002). Recent results demonstrated that the oscillation amplitude experiences either exponential or Gaussian time decay (Hood et al 2013;Pascoe et al 2016), however in a number of cases it is difficult to distinguish between these two scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Ruderman & Roberts 2002;Goossens et al 2002). Recent results demonstrated that the oscillation amplitude experiences either exponential or Gaussian time decay (Hood et al 2013;Pascoe et al 2016), however in a number of cases it is difficult to distinguish between these two scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…McEwan et al (2008) derived an analytical expression for the dependence of the period ratio on the density scale height, which was previously solved numerically by Donnelly et al (2006) and Díaz et al (2007) for loops, and by Donnelly et al (2007) for a magnetic arcade. A spatially resolved observation of the fundamental and second harmonic standing kink modes in a coronal loop was recently reported by Pascoe et al (2016), with a period ratio P 1 {2P 2 " 1.15˘0.22.…”
Section: Introductionmentioning
confidence: 81%
“…The time of the switch between damping profiles depends on the loop density contrast ratio, such that the Gaussian damping profile is the dominant one for low contrast loops, and the exponential profile dominant for high contrast loops (see also reviews by Pascoe 2014;De Moortel et al 2016). Pascoe et al (2016b) examined the damping profile of standing kink oscillations observed by SDO/AIA and found examples of both Gaussian and exponential damping behaviour. Pascoe et al (2013a) proposed that a unique seismological inversion for the transverse density profile would be possible in cases of oscillations for which both regimes were observed.…”
Section: Introductionmentioning
confidence: 99%
“…4. Pascoe et al (2016b) studied the damping profile of kink oscillations compiled by Goddard et al (2016) to demonstrate the existence of the Gaussian damping regime predicted by numerical (Pascoe et al 2012(Pascoe et al , 2013a and analytical (Hood et al 2013) modelling of mode coupling. One of the requirements for that investigation was for the oscillating loop to have a period of oscillation that remains stable over several cycles so that the damping profile could be accurately examined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation